2024
DOI: 10.1101/2024.03.20.585866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large diversity in the O-chain biosynthetic cluster within populations of Pelagibacterales

Jose M. Haro-Moreno,
Mario López-Pérez,
Carmen Molina-Pardines
et al.

Abstract: In this study, we have used single-amplified genomes (SAGs) and long-read metagenomics to examine the intrapopulation diversity of the O-chain polysaccharide biosynthesis cluster (OBC) in marine bacteria of the Pelagibacterales order. OBCs are notorious for their diversity and have been used to type strains in pathogens and saprophytes, but their patterns of variation in free-living bacteria are little known. We found that, for these major photoheterotrophic bacteria, the diversity is comparable to that of sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
1
2
0
Order By: Relevance
“…Indeed, a pangenome graph of our Pelagibacteraceae SAGs demonstrated that their HVR2 regions were nearly unique to individual cells (Fig. S10), as also reported in a recent study of marine Pelagibacteraceae (71). Unlike the fluctuating abundance of copiotrophs, oligotrophs are less likely to be affected by population bottlenecks and thus maintain their genetic microdiversity (7).…”
Section: Contrasting Viral Defense Strategies Of Oligotrophs and Copi...supporting
confidence: 80%
“…Indeed, a pangenome graph of our Pelagibacteraceae SAGs demonstrated that their HVR2 regions were nearly unique to individual cells (Fig. S10), as also reported in a recent study of marine Pelagibacteraceae (71). Unlike the fluctuating abundance of copiotrophs, oligotrophs are less likely to be affected by population bottlenecks and thus maintain their genetic microdiversity (7).…”
Section: Contrasting Viral Defense Strategies Of Oligotrophs and Copi...supporting
confidence: 80%
“…However, the most common version of this fGI (36 LRs) was not similar to the one of the Pacific Ocean isolate, with a deletion of most of the ORFs present in the SPOT01 genomic island (94%) (Figure 2B, lower part). Either for N. brevis or for N. catalinensis, the diversity of sequence of the glycosylation fGIs was much lower than that found in other microbes (Coleman et al 2006; Haro-Moreno et al 2024). However, in both cases, there seems to be decreased synteny towards the center of the island.…”
Section: Resultsmentioning
confidence: 83%
“…In a recent study, some of us have studied the diversity of O-chain polysaccharide genomic islands in Pelagibacterales (heterotrophic bacteria) and have found a very large diversity, reaching easily 130 different gene clusters in a single population (single species single sample) (Haro-Moreno et al, 2024). This is in sharp contrast to the results described here for a chemolithotrophic archaeon.…”
Section: Discussionmentioning
confidence: 99%